Islam dan Nasionalisme: Pandangan Pembaru Pendidikan Islam Tentang Nasionalisme (Kasus Ahmad Dahlan dan Abdul Wahab Khasbullah) - Iwan Setiawan (Universitas Muhammadiyah Makassar, 2017)
Abstract. Until this day, the dichotomy between “Islam” and “Nationalist” is still realized. The dichotomy makes the moslems not safe on their social communities, especially with the other religions in Indonesia. Finally, that dichotomy makes one big question, “Is Islam not nationalist?” This article tries answered “Islam is not nationalist?” by looking back on the history of two founding fathers of the islamic education and nation heroes. They are Ahmad Dahlan and Abdulwahab Khasbullah, the founders of two the biggest Islamic organization in Indonesa, Muhammadiyah and Nahdlatul Ulama (NU). By studying about two founder of islamic education in the colonalism era or before the independence of Indonesia, we can answered and explain the question above. The purpose of this article is to proofing that the islamic leader, Ahmad Dahlan and Abdulwahab Khasbullah are nationalist. Keywords: Pembaharu Pendidikan Islam, Nasionalisme, Ahmad Dahlan, Abdulwahab Khasbullah.